Enhancing the Usability of ITG Virtual Tour Website Through UI/UX Design Using the Five Planes Method - Ridwan Setiawan; Muhamad Faturrahman; Yosep Septiana; Dewi Tresnawati; Ade Sutedi (Teknika, 2025)
The virtual tour website in higher education significantly enhances campus information accessibility; yet, the poor usability of the ITG Virtual Tour website leads to a subpar user experience. This research offers a redesign of the UI/UX utilizing the Five Planes technique, which prioritizes clarity in information and navigation. A System Usability Scale (SUS) was employed to evaluate the site's usability prior to and after the redesign, adhering to the five stages of The Five Planes: Strategy, Scope, Structure, Skeleton, and Surface. The test findings indicated that the initial SUS score of 51.17 (classified as "poor") rose to 74.7 (classified as "good") following the installation of the revised design, demonstrating a substantial enhancement in usability and user satisfaction. This study contributes by demonstrating how the Five Planes method can be effectively applied in the academic context to improve the usability of virtual tour websites, offering a structured framework that can be adopted by other institutions seeking similar improvements.